Cutaneous lesions in pet rabbits following subcutaneous administration of a novel bivalent vaccine against myxomatosis and rabbit haemorrhagic disease. Issue 6 (16th September 2014) - Selleri, Paolo; Di Girolamo, Nicola; Vögtlin, Andrea; Fileccia, Ivan; Hoop, Richard; Bongiovanni, Laura
<x xml:space="preserve">Abstract</x> Background A novel bivalent vaccine to protect against myxomatosis and rabbit haemorrhagic disease is commercially available for pet rabbits. Hypothesis/Objectives To describe the appearance of cutaneous lesions arising in pet rabbits positive for myxoma virus (MV) by RT‐PCR evaluation shortly after vaccination. Animals Four pet rabbits presenting with papular, crusting skin lesions 10 days after vaccination. Methods Histological evaluation of formalin‐fixed skin biopsies obtained from lesional skin (case 1). Real‐time polymerase chain reaction (RT‐PCR) evaluation of paraffin‐embedded tissue from skin biopsies (case 1) and crusts obtained from the lesion surface (cases 2–4) for myxoma virus are reported as cycle threshold (Ct) values. Results Lesions affecting the ear pinna, dorsal aspect of the nose, vulva and/or conjunctiva are reported. Histopathological findings included severe ulcerative, necrotizing dermatitis and intralesional cytoplasmic inclusion bodies in myxoma cells. DNA was amplified from all the paraffin‐embedded skin biopsies (Ct = 34–35) and crusts (Ct = 20–24). Conclusions and clinical importance Although a wild virus challenge cannot be definitively excluded, veterinarians and pet‐owners should be aware that cutaneous lesions have been observed after vaccination with this novel vaccine in low numbers of rabbits.